Landscape Rehabilitation And Ecological Problems Of Tashkent City (Eurasian Journal of Engineering and Technology, 2025)
This article discusses the identification of degraded ecological layers of the Tashkent urban environment and ways to restore them. Based on international experience, local ecological situation, current air quality indicators, and scientific analyses of the natural balance, rehabilitation approaches suitable for Tashkent conditions have been developed. The main part of the article shows that if the urban landscape is purposefully restored, air quality will stabilize, wind circulation will be restored, and green infrastructure will become a real protective layer for the health of the population